Enteroparasites, epidemiological indicators and nutritional status in preschoolers of “Coropo”, Aragua State, Venezuela abstract (Revista Venezolana de Salud Pública, 2018)
Parasitic diseases affect millions of people worldwide, most commonly in children, are closely linked to poverty and other socio-economic factors. The study aimed to establish the relationship between intestinal parasites, and epidemiological and nutritional status in preschool educational institutions of the municipality Coropo, Aragua, Venezuela. We evaluated 145 children and their feces were analyzed using the techniques of physiological saline, Lugol, Kato, Faust, Baermann and Graham. Nutritional assessment was performed using clinical evaluation and anthropometric indicators, with the cut offs, excess: > p90; Normal: between p10 and p90; deficit: 0.05). However, they observed a statistically significant association (p
Keywords: Enteroparasites; pre-school